Analisis Beberapa Faktor Yang Mempengaruhi Kinerja Karyawan (Studi Pada PDAM Kabupaten Purbalingga) - Wibowo, Anggun Nurochmah Putri, Drs.Kusdiyanto M.Si (2017)
ABSTRACT This study uses a quantitative tell pedekatan employee perceptions in terms of leadership style, discipline applied and works of environment to the performance of the company. In this study took samples at Purbalingga. The sample used in this study were 50 respondents. This analysis tool as a whole is a statistical description, test instrument data, and multiple linear regression. The results of the analysis obtained regression equation is Y = -4.004 + 0.420 X1 + 0.355 + 0.366 X2 X3 + e on leadership style variable has a value of 0.026, the discipline of work to the value of 0.019, and a work environment that all the variable value of 0,031 is smaller than 0, 05 then partially have a significant influence on the performance of employees of. PDAM Purbalingga. Simultaneously have a significant influence on employee performance